BENARKAH ADA “REPUBLIK” LANFANG KONGSI DI KALIMANTAN BARAT ? - sugiri kustedja (Jurnal Sosioteknologi, 2016)
ABSTRACT There was an organization Lanfang Kongsi 蘭 芳 公 司, (1777-1884), in western Kalimantan island, belong to Chinese diaspora gold miners. Some western researchers says it runs with the democratic republic system. It has very unique decision making process and the way to choose their chief and staff. This paper shows the cultural background which proved as the dominant element in cohesiveness of kongsi members. Lan Fang Kongsi founding and the end of it by the Dutch occupation. A discussion of possibility models which system has been adopted and copied for the kongsi operation, too early in the time to be copied from any existing Wetern democratic republic. Keywords: Lanfang Kongsi, history of western Kalimantan, Chinese diaspora, gold mine, democracy, republic. ABSTRAK Dalam sejarah Kalimantan Barat pernah berdiri perkumpulan beranggotakan para penambang emas Tionghoa : Lanfang Kongsi 蘭 芳 公 司, (1777-1884). Kongsi memiliki cara pengelolaan yang oleh beberapa peneliti Barat disamakan dengan sistim pemerintahan demokrasi republik. Tulisan ini menguraikan latar belakang budaya anggota kongsi yang menjadi perekat mempersatukan para anggotanya. Bentuk organisasi dan mekanisme pengambilan putusan dan pemilihan Ketua serta para pengurus. Awal pendirian dan berakhirnya kongsi ini karena diduduki pemerintah kolonial Belanda. Paper diakhiri dengan diskusi kemungkinan model acuan yang telah ditiru untuk menjalankan sistim pengelolaan kongsi, sebelum adanya contoh tata negara demokrasi barat terbentuk.